Microsatellite DNA Analysis on the Polyandry of Green Sea Turtle Cheloniamydas - DEWI PURNAMA; NEVIATY PUTRI ZAMANI; ACHMAD FARAJALLAH (HAYATI Journal of Biosciences, 2013)
Green turtle (Cheloniamydas; Testudines) is included in the group of polyandryanimals, which is single female mated with many male. DNA polymorphism method generally considered to have a high degree of accuracy as compared to other methods to elucidate polyandry phenomena on many animals. In this research, three microsatellite loci were used to identify the number and frequency of genotypes per locus, the number and frequency alleles per locus, and genotypes and number of alleles in the nest. The purpose of this research was to study the reproductive pattern of Cheloniamydas and compensation eggs of males from hatchling’s population in turtle conservation area of Pangumbahan Coastal Park, West Java. The result showed that from 10 nests, we could find 37 genotypes with 11 alleles for D108 locus, 21 genotypes with 9 alleles for B103 locus, and 27 genotypes with 9 alleles for C102 locus. The alleles number of each nest was more than 5 alleles for 5 nests, and more than 4 alleles for the remaining nests. Based on the probabilities of alleles contribution of each parent, the green turtle was polyandry animals.